Mechanical Properties of Cocos nucifera Wood Planted Around Mt. Merapi, Yogyakarta - Ali Awaludin; J.P. Gentur Sutapa (Masyarakat Peneliti Kayu Indonesia, 2012)
This study presented test results of mechanical properties of Cocos nucifera wood that were planted around Mt. Merapi, Yogyakarta. The test specimens were obtained from trees that had been exposed to pyroclastic flow during the 2010 volcanic eruption as indicated by dark colour of the outer bark. Test set-up was designed according to ASTM D143-94 and the mechanical properties, which are determined based on the lower 5% exclusion limit, were bending strength, shear strength, dowel bearing strength and compressive strength. Results of the specific gravity measurement showed significant variation of specific gravity between the inner part (close to the pith) and the outer part (far from the pith) in a cross-section. Since mechanical properties generally depend upon specific gravity, it was decided to divide the wood specimens into two groups: specimens from the inner part and specimens from the outer part. Most of the mechanical properties of wood specimens from the inner part, except for bending strength, were found to be much lower than E10 grade of the Indonesian National Standard (SNI). Hence it is not recommended for any structural use. In the case of wood specimens from the outer part, their mechanical properties were as follows: bending strength 83.66 MPa; shear strength parallel to grain 4.41 MPa; dowel bearing strength parallel to grain 40.65 MPa; dowel bearing strength perpendicular to grain 25.88 MPa, compressive strength parallel to grain 37.89 MPa; and compressive strength perpendicular to grain 7.48 MPa. It seemed that the wood specimens from the outer part had excellent mechanical properties especially in bending, but their shear strength is extremely low.